Negotiating Love Languages in Digital Romantic Relationships: A Phenomenological Study of Generation Z Couples in Yogyakarta - Meilinda Papuanita Ully; Devi Wening Astari (FAKULTAS DAKWAH UIN SALATIGA, 2025)
Forming a romantic relationship at a young age is a complex process, requiring the search for personal meaning, emotional adjustment, and customized communication techniques. This research examines the dynamics of love language communication through social media and the socio-cultural aspects of expressing affection among Generation Z in Yogyakarta. The research employed a qualitative methodology with a phenomenological Moustakas perspective. Data were collected via in-depth interviews with four men and seven women, Gen Z, a total of 11 informants who were selected using snowball sampling methods. The results suggest that quality time and acts of service are the two most prevalent forms of love language, as they are seen as effective in creating emotional closeness and showcasing genuine care. This preference for limited physical touch in public spaces is consistent with Yogyakarta’s cultural values, which emphasize politeness. Research suggests that platforms like TikTok, WhatsApp, and Instagram contribute to romantic expectations and the use of love language, though they are not the key players in relationship dynamics. Establishing open communication is crucial for reconciling disparities in love preferences and sustaining long-term relationships amidst cultural and technological advancements.